CONCEPTIONAL FOUNDATIONS OF THE DEVELOPMENT OF BUSINESS EDUCATION IN THE REPUBLIC OF TATARSTAN - T. A. Sharifullina (Russian Journal of Economics and Law)
The articles states reasons determining the necessity of business-education as a multilevel system. The first reason is the necessity of a dramatic reformation of the higher professional educational system with its orientation towards the Tatarstan national interests. The second reason is the dynamic character of the process of acquiring the corresponding knowledge and skills, based on the principles of continuity and succession in various forms, with various purposes and at various ages. The third one is the transformation of business-education into a separate sector of educational services lead by the market demand.